Functions for S. cerevisiae Swd2p in 3′ end formation of specific mRNAs and snoRNAs and global histone 3 lysine 4 methylation - DICHTL, BERNHARD (Copyright 2004 by RNA Society, 2004)
The Saccharomyces cerevisiae WD-40 repeat protein Swd2p associates with two functionally distinct multiprotein complexes: the cleavage and polyadenylation factor (CPF) that is involved in pre-mRNA and snoRNA 3′ end formation and the SET1 complex (SET1C) that methylates histone 3 lysine 4. Based on bioinformatic analysis we predict a seven-bladed β-propeller structure for Swd2p proteins. Northern, transcriptional run-on and in vitro 3′ end cleavage analyses suggest that temperature sensitive swd2 strains were defective in 3′ end formation of specific mRNAs and snoRNAs. Protein–protein interaction studies support a role for Swd2p in the assembly of 3′ end formation complexes. Furthermore, histone 3 lysine 4 di-and tri-methylation were adversely affected and telomeres were shortened in swd2 mutants. Underaccumulation of the Set1p methyltransferase accounts for the observed loss of SET1C activity and suggests a requirement for Swd2p for the stability or assembly of this complex. We also provide evidence that the roles of Swd2p as component of CPF and SET1C are functionally independent. Taken together, our results establish a dual requirement for Swd2p in 3′ end formation and histone tail modification.